House Prices and the stance of Monetary Policy. - Marek Jarociński; Frank Smets (European Central Bank (ECB), 2008)
This paper estimates a Bayesian VAR for the US economy which includes a housing sector and addresses the following questions. Can developments in the housing sector be explained on the basis of developments in real and nominal GDP and interest rates? What are the effects of housing demand shocks on the economy? How does monetary policy affect the housing market? What are the implications of house price developments for the stance of monetary policy? Regarding the latter question, we implement a version of a Monetary Conditions Index (MCI) due to Céspedes et al. (2006).
Keywords: E3; E4; 330; Bayesian VAR; conditional forecast; House prices; monetary conditions index; monetary policy shock; Immobilienpreis; Geldpolitik; Makroökonometrie; Nationaleinkommen; Zins; USA